2012
DOI: 10.1021/jf3001839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing on Recovery and Variability Associated with Immunochemical Analytical Methods for Multiple Allergens in a Single Matrix: Sugar Cookies

Abstract: Among the major food allergies, peanut, egg, and milk are the most common. The immunochemical detection of food allergens depends on various factors, such as the food matrix and processing method, which can affect allergen conformation and extractability. This study aimed to (1) develop matrix-specific incurred reference materials for allergen testing, (2) determine whether multiple allergens in the same model food can be simultaneously detected, and (3) establish the effect of processing on reference material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…The production process of these fining agents include the use of heat, acid extraction, and enzymatic hydrolysis, leading to commercial products containing proteins that range from a native to a highly denatured stage. More generally, the importance of food processing on the detection of allergens in food by ELISA has been reported by several authors (Diaz‐Amigo ; Downs and Taylor ; Garber and Perry ; Khuda and others , ). Antibody–antigen binding may be affected by a modification of the antigen structure occurred during food processing.…”
Section: Resultsmentioning
confidence: 76%
“…The production process of these fining agents include the use of heat, acid extraction, and enzymatic hydrolysis, leading to commercial products containing proteins that range from a native to a highly denatured stage. More generally, the importance of food processing on the detection of allergens in food by ELISA has been reported by several authors (Diaz‐Amigo ; Downs and Taylor ; Garber and Perry ; Khuda and others , ). Antibody–antigen binding may be affected by a modification of the antigen structure occurred during food processing.…”
Section: Resultsmentioning
confidence: 76%
“…Eissa and others () developed an immunosensor able to detect down to 0.85 pg/mL of β‐LG in food products, which is the lowest LOD reported for this protein by electrochemical immunosensors (Table ). Nonetheless, owing to the fact that these systems are based on the biological interaction between an antibody and the respective allergen/marker protein, a careful interpretation is always needed to avoid false positive or false negative results (Johnson and others ; Costa and others ; Khuda and others ; Gomaa and Boye , ).…”
Section: Analytical Methods For the Detection Of Milk Allergens In Prmentioning
confidence: 99%
“…Thermal processing of peanut flour reduced the protein solubility and the ability of ELISA kits to accurately quantify peanut depending on the peanut allergen targeted by the antibody (Fu & Maks, ). Several studies have reported reduced recovery of peanut proteins by commercial ELISA kits when the peanut source is thermally treated or incurred food samples had undergone thermal processing during food preparation (Jayasena et al., ; Khuda et al., ; Parker et al., ). Moreover, extraction buffer components and extraction conditions can also affect protein structure, contributing to altered immunoreactivity.…”
Section: Introductionmentioning
confidence: 99%